Sylepta balteata F. (Pyralidae, Lepidoptera), an Important Pest of Kullu, Sterculia urens Roxb., (Sterculiaceae) - Amin, P. W.; Upadhyaya, A. K. (Indian Forester, 1977)
Leaves of Sierculia urena an important tree species yielding valuable gum "karaya", were found to be sverely destroyed by hitherto unreported insect. Sylepta balteala F. The damage was between 25 to 100 percent. The attack was predominant from March to October, and 5 overlapping generations were produced during the year. The life cycle was completed with in 25 to 36 days with egg, inrval, and pupal perioda being 3-4, 14-16, and 7-8 days.